Activation by adrenaline of a low-conductance G protein-dependent K+ channel in mouse pancreatic B cells. - Rorsman, P; Bokvist, K; Ammälä, C; Arkhammar, P; Berggren, P; Larsson, O; Wåhlander, K (1991)
Insulin is produced and secreted by the B cells in the endocrine pancreas. In vivo, insulin secretion is under the control of a number of metabolic, neural and hormonal substances. It is now clear that stimulation of insulin release by fuel secretagogues, such as glucose, involves the closure of K+ channels that are sensitive to the intracellular ATP concentration (KATP channels). This leads to membrane depolarization and the generation of Ca2(+)-dependent action potentials. The mechanisms whereby hormones and neurotransmitters such as adrenaline, galanin and somatostatin, which are released by intraislet nerve endings and the pancreatic D cells, produce inhibition of insulin secretion are not clear. Here we show that adrenaline suppresses B-cell electrical activity (and thus insulin secretion) by a G protein-dependent mechanism, which culminates in the activation of a sulphonylurea-insensitive low-conductance K+ channel distinct from the KATP channel.